Facetas discursivas em torno da criminalização da homofobia e da transfobia - TAVARES, Raylton Carlos de Lima (2021)
This paper analyzes a chain of discursive events surrounding the Brazilian Federal Supreme Court's decision to classify homophobia and transphobia as a crime. The research is based on the theoretical-methodological architecture of Critical Discourse Studies. The corpus is composed of three texts of the newspaper O Antagonista, analyzed mainly in the light of the language of description of the Transitivity system. The results indicate that the representation thematizes more the possible discontent of religious than the benefits to the LGBTQI+ community, and that there are ideological meanings that operate through the concealment and purge of the other, working to maintain the state of violence against LGBTQI +.